Declining Democracy and Constrained Voices: A Habermasian and Foucauldian Critique of Indonesian Freedom of Expression - Pesurnay, Althien John; Fuad, Zamzam Muhammad (Jurnal Filsafat "WISDOM", 2025)
This article analyzes the state of freedom of expression in the context of democratic decline in Indonesia, using the concepts of Jurgen Habermas's public sphere and Michel Foucault's governmentality. The aim is to defend the basic principles of democracy by emphasizing the urgency of freedom of expression to respond to this political condition. Habermas's idea of the public sphere emphasizes the importance of a rational and open discussion space to encourage the formation of deliberative democracy. Meanwhile, Foucault's idea of governmentality will be employed to understand how the state produces regulations and disciplines citizen behavior through certain discourses for certain interests. This article shows that the practice of freedom of expression in Indonesia has been constrained by regulations in the form of rules and regulations and subtle discursive practices, such as the mainstreaming of democratic politeness discourse. The first part of this article discusses the relationship between Indonesia's democratic regression and the situation of freedom of expression in Indonesia. The second part is an assessment of the situation of freedom of expression using Habermas's concept of the public sphere. The third part focuses on the governmentality practices carried out by the state to repress freedom of expression.